Analysis of Cup Printing Quality Control Using Statistical Process Control Methods and Human Reliability Assessment (Case Study: PT Indo Ceria Plastic Printing) - Moch Imam Andreansyah; Atikha Sidhi Cahyana (Procedia of Engineering and Life Science, 2022)
This research was conducted at PT Indo Ceria Plastic Printing aims to determine the main cause of defective cup printing and to reduce product defects in the production process. Based on the problems faced by the company, namely the high percentage of cup printing defects which eventually led to more and more reject cup printing rates, even the problem of passing the defective cup being sent to the customer’s hands, which made the customer complain about the problem of the number of bad product quality being sent so that they finally submitted a returned product. Therefore, quality control efforts are carried out on cup printing products to find the cause of the defect and find a solution to repair it. The research methods used in solving the problems that occur at PT Indo Ceria Plastic Printing is to use Statistical Process Control methods and Human Reliability Assessment. From the result of research conducted, it is known that the biggest cause of defect in cup printing products is “defect awal start”. From the results of meaning employee performance, the largest HEP value was found, namely, the type of possible error is “pengisian tinta pada mesin” which was 0,6324. So, this factor was the dominant one that resulted in defects and must be repaired immediately.